Same Day Discharge Strategy for Primary Percutaneous Coronary Intervention: A Safety and Feasibility Approach - Jehangir Ali Shah; Tahir Saghir; Bashir Ahmed; Syed Alishan ul Haq; Rajesh Kumar; Muhammad Naeem Mengal; Mehwish Zehra; Syeda Sakeena Raza; Musa Karim; Nadeem Qamar (Current Overview on Disease and Health Research Vol. 9, 2023)
This chapter aims to assess the safety of early discharge after primary percutaneous coronary intervention (PCI) in selected low-risk patients in the population of Karachi, Pakistan. In this study, 600 low-risk patients who underwent primary PCI and were released within 48 hours were continuously monitored for major adverse cardiac events (MACE) after 7, and then after 30 days. In this study, the sample consisted of 81.8% (491) male patients with mean age of 54.89 ± 11.08 years. Killip class was I in 90% (540) of the patients. The findings showed that majority of patients (84%) were discharged within 24 hours of the procedure. Loss to follow-up after rate at 7 and 30 days was 4% (24) and 4.3% (26) respectively. Cumulative MACE rate after 7 and 30 days was noticed in 3.5% and 4.9%, all-cause mortality in 1.4% and 2.3%, cerebrovascular events in 0.9% and 1.4%, unplanned revascularization in 0.9% and 1.2%, re-infarction in 0.3% and 0.5%, unplanned re-hospitalization in 0.5% and 0.5%, and bleeding events in 0.5% and 0.5% of the patients respectively. It was discovered that very early (\(\) 24 hours) discharge after primary PCI for low-risk patients is a safe method when subjected to careful pre-discharge risk assessment, with a low rate of MACE after 7 and 30 days.